HUBUNGAN STATUS GIZI DENGAN KEJADIAN HIPERTENSI DI PUSKESMAS LUBUK BUAYA TAHUN 2022 - Yusti Siana; Almurdi; Muhammad Iqballisandi; Dian Puspita (Nusantara Hasana Journal, 2023)
Hypertension is a degenerative disease that has a high level of morbidity and mortality and is characterized by an increase in blood pressure above normal values. Increased blood pressure is caused by many factors, such as weight, nutritional status, genetics, gender, and smoking habits. There was a significant increase in cases of hypertension in Indonesia in the period 2013-2015, while in West Sumatra during the period 2013-2015 there was an increase of 8.3%. This study aims to determine the relationship between nutritional status and the incidence of hypertension at the Lubuk Buaya Public Health Center, Padang City. This study uses a quantitative descriptive method with a cross-sectional approach using primary data with a sample of 85 respondents. Based on the results of data analysis, it was found that the most common hypertension was grade 1 hypertension, namely 48 (56.5%) respondents. The age group that experienced the most hypertension was the age group >45 years, with (94.1%) respondents. The most affected gender group who suffer from hypertension are women, with 62 (79.2%) respondents. Nutritional status as measured by BMI was found to be in the highest category with overweight, namely 49 (55,7) respondents, and the results of data processing using the chi-square test obtained a p value of 0.042, where p value was less than p (0.05). There is a significant relationship between nutritional status and the incidence of hypertension that occurred at the Lubuk Buaya Health Center, where p value = 0.042 was obtained from the test results using the chi-square test.